PENGARUH LOYALITAS ANGGOTA KOPERASI TERHADAP PELAYANAN PENGURUS PADA KOPERASI PEGAWAI NEGERI UNIVERSITAS TANJUNGPURA - Marina, Repalina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe purpose of this research is to know the influence of loyalty of the cooperative members to the servise of the management of the civil servise cooperative (kpn) of the university of tanjungpura pontianak. The method in this research is the descriptive method. This is an ex post facto reasearch. The population in this research is 1475members. The number of samples in this reasearch is 94 members. Data collection techniques in this reasearch are direct communication techniques (interview guidelines), indirect communication techniques (questionnaire), and documentary techniques (data of members ). The results of this research showed that there is the positive influence ofloyalty of the cooperative members to the servise of the management of the civil servise cooperative (kpn) of the university of tanjungpura pontianak.. This can be known from the t value is 9.472 which shows there is influence of members basic training towards members responsibility and obligation outcome. When it compared with the t table on the significance level of 0.05 of 1.989, so that Ha is accepted. The conclusion of this research is of loyalty of the cooperative members to the servise of the management of the civil servise cooperative (kpn) of the university of tanjungpura pontianak.Â Keywords: loyalty of the cooperative members, civil servise , cooperative